(untitled) (Anwer Khan Modern Medical College Journal, 2011)
This study had been planned to see the histomorphological pattern of gastric mucosal biopsy, demonstrate the organism H .Pylori and correlate with endoscopic findings. The study was carried out in the department of the Pathology Rajshahi Medical College, Rajshahi, Bangladesh, during the period from January 2006 to December 2007. Endoscopic biopsy specimens were obtained from 105 cases of gastro duodenal lesions. According to endoscopic findings out of 105 cases 69(65.7%) had gastric carcinoma, 06 (5.71%) had gastric ulcer, 05 (4.76%) had duodenal ulcer, 05 (476%) had gastritis and 20 (19.04%) had normal mucosa, reported as non-ulcer dyspepsia. Of the 69 endoscopically gastric carcinoma 59 (85.50%) were diagnosed histologically as adenocarcinoma and 10 (14.50%) were diagnosed histologically as chronic gastritis in which H.Pylori was positive in 27.5% and 14.50% positive in chronic gastritis. Of 06 gastric ulcer 03 (50%) was diagnosed histologically as gastritis and 03 (50%) were diagnosed histologically as gastric carcinoma. H. Pylori was positive in cent percent of gastritis. Of 05 duodenal ulcer 03 (60%) were diagnosed histologically as gastritis and 02 (40%) were diagnosed histologically as intestinal metaplasia H. Pylori was positive in 66.6% of duodenal ulcer. Of 05 gastritis were diagnosed histologically as gastritis 60% were postive for H.Pylori. Of 20 NUD 18 (90%) were diagnosed histologically as gastritis, 01 (05%) was diagnosed histologically as ulcer and 01 (05%) was diagnosed histologically as normal mucosa, all these cases no H. Pylori was found. Key Words: Helicobacter Pylori; Gastroduodenal Lesion; Association DOI: http://dx.doi.org/10.3329/akmmcj.v2i2.8164 AKMMC J 2011; 2(2): 06-10